2018
DOI: 10.1111/fcp.12342
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of fenofibrate against ischemia‐/reperfusion‐induced cardiac arrhythmias in isolated rat hearts

Abstract: Fenofibrate is a peroxisome proliferator-activated receptor (PPAR)-α activator that lowers triglycerides and influences cytochrome P-450 (CYP-450) epoxygenase-dependent arachidonic acid (AA) metabolism. CYP-450 epoxygenase metabolizes AA to epoxyeicosatrienoic acids (EETs). EETs have coronary dilating and cardiac and renal protective properties. Fibrates possess similar properties due to their CYP-450 epoxygenase-inducing properties that lead to increase in endogenous EET production. In the current investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…However, on co‐administration of FEN to BPH induced group (group V) showed moderate increase in apoptosis explaining the preservation and protection of prostatic tissue. These results are in agreement with previous studies which showed apoptotic effect of FEN in different models .…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…However, on co‐administration of FEN to BPH induced group (group V) showed moderate increase in apoptosis explaining the preservation and protection of prostatic tissue. These results are in agreement with previous studies which showed apoptotic effect of FEN in different models .…”
Section: Discussionsupporting
confidence: 94%
“…These findings are in line with previous studies . On co‐administration of FEN with BPH, there is marked improvement of the measured antioxidant and oxidant parameters indicating the protective effect of FEN against formation of free radicals which is supported by different studies .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations